Determination of Natural Radioactivity in Soil Samples around Gold Mining Area in Khamkeut District, Bolikhamxay Province,Laos Using Gamma Ray Spectrometer with NaI (Tl) Detector - Leuangtakoun, Somsavath; Hong, Bui Thi; Van Loat, Bui; Cuong, Phan Viet (VNU Journal of Science: Mathematics - Physics; Vol 34 No 3DO - 10.25073/2588-1124/vnumap.4270, 2018)
This paper presented the method of determining the radioactivity of 40 K, 226 Ra and 232 Th in soil samples by gamma-ray spectrometer using NaI (Tl) scintillation detector. The radioactivity of each isotope is calculated based on the net count rate in the energy window characteristic for the 40 K, 226 Ra and 232 Th radioisotopes respectively. We have determined  activity concentrations of the natural radionuclides 226 Ra, 232 Th and 40 K in 15 soil samples collected around gold mines of Khamkeut district, Bolikhamxay Province, Laos. The average activity concentrations of the natural radionuclides 226 Ra, 232 Th and 40 K are 46.58  ±  7.36 , 71.19  ±  5.42 and 574.62  ±  25.02 Bq.kg -1 , respectively. The average activity concentrations of 226 Ra and 232 Th in this work are higher than those of Bolikhamxay Province, Laos and the world average values. The estimated average outdoor annual effective dose (E) and radium equivalent actitvity (Ra eq ) are 0.10  ±  0.004 mSv.yr -1 and 192.64  ±  16.12 Bq.kg -1 , respectively.